Single-cell transcriptional landscapes of bovine peri-implantation development - Giovanna Nascimento Scatolin; Hao Ming; Yinjuan Wang; Rajan Iyyappan; Emilio Gutierrez-Castillo; Linkai Zhu; Masroor Sagheer; Chao Song; Kenneth Bondioli; Zongliang Jiang (iScience, 2024)
Summary: Supporting healthy pregnancy outcomes requires a comprehensive understanding of the molecular and cellular programs of peri-implantation development, when most pregnancy failure occurs. Here, we present single-cell transcriptomes of bovine peri-implantation embryo development at day 12, 14, 16, and 18 post-fertilization. We defined the cellular composition and gene expression of embryonic disc, hypoblast, and trophoblast lineages in bovine peri-implantation embryos, and identified markers and pathway signaling that represent distinct stages of bovine peri-implantation lineages; the expression of selected markers was validated in peri-implantation embryos. Using detailed time-course transcriptomic analyses, we revealed a previously unrecognized primitive trophoblast cell lineage. We also characterized conserved and divergence peri-implantation lineage programs between bovine and other mammalian species. Finally, we established cell-cell communication signaling underlies embryonic and extraembryonic cell interaction to ensure proper early development. These data provide foundational information to discover essential biological signaling underpinning bovine peri-implantation development.